1978
DOI: 10.3109/03008207809152626
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Maturation and Age on Mechanical and Biochemical Parameters of Connective Tissue of Various Organs in the Rat

Abstract: The mechanical and biochemical parameters of connective tissue components of several organs in rats, e.g. skin, tail tendons and aorta, have been compared. Organ samples have been analyzed at various ages allowing investigation of the changes during maturation and senescence. The age dependent changes in the various organs were quite similar. The parameters indicating strength and elasticity, e.g. ultimate load, ultimate strength, ultimate strain, modulus of elasticity and rate of load increase, rose sharply d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
41
1

Year Published

1983
1983
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(53 citation statements)
references
References 22 publications
11
41
1
Order By: Relevance
“…The physical properties of collagen are very dependent on cross-links within and between the collagen molecules. During maturation, the number and quality of the cross-links increase, which increases the tensile strength and reduces collagen solubility (Piez 1968, Vogel 1978, Viidik et al 1982. The effect of NSAID may be due to interference with collagen metabolism and crosslinking in the process of healing.…”
Section: Discussionmentioning
confidence: 99%
“…The physical properties of collagen are very dependent on cross-links within and between the collagen molecules. During maturation, the number and quality of the cross-links increase, which increases the tensile strength and reduces collagen solubility (Piez 1968, Vogel 1978, Viidik et al 1982. The effect of NSAID may be due to interference with collagen metabolism and crosslinking in the process of healing.…”
Section: Discussionmentioning
confidence: 99%
“…While age-related sarcopenia has been repeatedly documented, the effect of aging on tendon biomechanical properties is inconclusive 74,[79][80][81][82][83] . Methodological differences make study comparisons difficult, although the majority of investigators have suggested that collagen loss occurs in older individuals [84][85][86] .…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…This suggests that work done by muscle within the muscle-tendon units at low speeds is progressively substituted, with increasing speed, with elastic energy storage and recovery by tendons (see section 4.4 and Figure 21). On average, the ratio t push /t brake is greater in the old subjects suggesting a less elastic behavior, possibly also due, at least in part, to changes in tendons mechanical properties caused by collagen reduction [86]. Modified from [36].…”
Section: Figure 25mentioning
confidence: 99%